2021
DOI: 10.1097/pcc.0000000000002785
|View full text |Cite
|
Sign up to set email alerts
|

Outcomes of Children With Firearm Injuries Admitted to the PICU in the United States*

Abstract: Firearm-related injury is the second leading cause of injury and death for children 1-18 years old in United States. The objective of our study was to analyze the outcomes of children admitted to the PICU with firearm injuries. DESIGN: Retrospective study.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
8
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 8 publications
(8 citation statements)
references
References 18 publications
0
8
0
Order By: Relevance
“…19 In the present study, the mortality rate was highest among those with self-directed firearm injuries than in the other groups, which is similar to the findings of earlier studies. [20][21][22] A continuous rise can be seen in cases of self-harm by firearms among children 20 , and previous studies have reported that firearm-related injuries contribute to the rate of disabilities among children, making gun violence an important public health issue. 7 Around half of all children hospitalized with firearm injuries are discharged with disabilities.…”
Section: Discussionmentioning
confidence: 99%
“…19 In the present study, the mortality rate was highest among those with self-directed firearm injuries than in the other groups, which is similar to the findings of earlier studies. [20][21][22] A continuous rise can be seen in cases of self-harm by firearms among children 20 , and previous studies have reported that firearm-related injuries contribute to the rate of disabilities among children, making gun violence an important public health issue. 7 Around half of all children hospitalized with firearm injuries are discharged with disabilities.…”
Section: Discussionmentioning
confidence: 99%
“…Historically, GSWs constitute 10% (interquartile range [IQR], 8-16%) of pediatric trauma activations at our center annually, with an average of 13.8% over the past 5 years. Although a recently published study characterized PICU mortality among pediatric GSW patients, risk factors for admission remain unclear (10). The primary objective of this study was to characterize mortality, likelihood of PICU admission, and risk factors associated with PICU admission among children with GSWs in a single urban academic center with a disproportionately high volume of pediatric firearm injury.…”
mentioning
confidence: 99%
“…According to Bagdure et al (5), Black children are about 14% of the patient population, but they suffer 45% of critical firearm injuries and 30% of firearm deaths in the PICU. Although White children had a higher overall mortality, it is disproportionately low compared with population representation.…”
mentioning
confidence: 99%
“…These data again highlight violence and firearm injury as a health disparity, reflecting systemic racism and structural inequality experienced by Black youth. The analyses by Bagdure et al (5) emphasize the continued need for comprehensive, accessible, and highly detailed national datasets on fatal and nonfatal firearm injuries in order to fully understand the magnitude of this public health problem (7).…”
mentioning
confidence: 99%
See 1 more Smart Citation